A very early diagnosis of Alstrӧm syndrome by next generation sequencing - Gatticchi, Leonardo (BMC Med Genet, 2020)
BACKGROUND: Alström syndrome is a rare recessively inherited disorder caused by variants in the ALMS1 gene. It is characterized by multiple organ dysfunction, including cone-rod retinal dystrophy, dilated cardiomyopathy, hearing loss, obesity, insulin resistance, hyperinsulinemia, type 2 diabetes mellitus and systemic fibrosis. Heterogeneity and age-dependent development of clinical manifestations make it difficult to obtain a clear diagnosis, especially in pediatric patients. CASE PRESENTATION: Here we report the case of a girl with Alström syndrome. Genetic examination was proposed at age 22 months when suspected macular degeneration was the only major finding. Next generation sequencing of a panel of genes linked to eye-related pathologies revealed two compound heterozygous variants in the ALMS1 gene. Frameshift variants c.1196_1202del, p.(Thr399Lysfs*11), rs761292021 and c.11310_11313del, (p.Glu3771Trpfs*18), rs747272625 were detected in exons 5 and 16, respectively. Both variants cause frameshifts and generation of a premature stop-codon that probably leads to mRNA nonsense-mediated decay. Validation and segregation of ALMS1 variants were confirmed by Sanger sequencing. CONCLUSIONS: Genetic testing makes it possible, even in childhood, to increase the number of correct diagnoses of patients who have ambiguous phenotypes caused by rare genetic variants. The development of high-throughput sequencing technologies offers an exceptionally valuable screening tool for clear genetic diagnoses and ensures early multidisciplinary management and treatment of the emerging symptoms.